Low admission blood pressure as a marker of poor 1-year survival in patients with revascularized critical limb ischemia. Issue 8 (August 2021) - Yannoutsos, Alexandra; Lin, Franck; Billuart, Olivier; Buronfosse, Anne; Sacco, Emmanuelle; Beaussier, Hélène; Mourad, Jean-Jacques; Emmerich, Joseph; Lazareth, Isabelle; Priollet, Pascal
Abstract : Objective: To contrast the association between blood pressure (BP) level and antihypertensive medications at hospital admission with 1-year mortality in patients undergoing revascularization for critical limb ischemia (CLI). Methods: From November 2013 to May 2019, 315 consecutive patients were retrospectively included. A median of seven (IQR 3–13) separate readings were recorded for each patient before revascularization procedure and the average represented patient's mean BP. BP-lowering medications, clinical and biological parameters were recorded at baseline. The main outcome was total 1-year mortality. Results: The cohort included 172 men (55%) and 143 women (45%), with a mean age of 77.9 ± 11.9 years. Treated hypertension was present in 245 (78%) patients; 288 (91%) patients had BP-lowering drug prescriptions (2.1 ± 1.3 medications at baseline). Mean SBP, DBP, mean BP (MBP) and pulse pressure (PP) were 132 ± 18, 70 ± 8, 90 ± 10 and 62 ± 16mmHg. During 1-year follow-up, 80 (25.4%) patients died. In single-pressure multivariate analysis, SBP (hazard ratio 0.97; 95% CI 0.96–0.99; P = 0.005), MBP (hazard ratio 0.96; 95% CI 0.92–0.99; P = 0.01), PP (hazard ratio 0.97; 95% CI 0.95–0.99; P = 0.009), but not DBP, were inversely correlated with 1-year mortality, independently of age, coronary heart disease, left ventricular ejection fraction, brain natriuretic peptide, serum albumin, institutionalized status and antihypertensive drugs. Association between SBP, MBP and PP with 1-year mortality had a quite linear reverse pattern. Conclusion: Among patients undergoing revascularization for CLI, there is an inverse correlation between admission SBP, MBP and PP with 1-year mortality. BP may represent a modifiable therapeutic target to prevent poor outcome in CLI patients.